Exploring the perceptions of drivers of energy behaviour - Van den Broek, Karlijn; Walker, Ian (Energy policy, 2019)
Many models have been applied to predict energy use and savings, yet few studies have investigated people's own perceptions of what drives their energy use. Understanding these perceptions can help design energy policy that is likely to be trusted and perceived as credible. This study assessed the perception of the drivers of energy use among young adults, who had recently become independent energy consumers, but were not yet paying for their energy bills. Focus groups were conducted in which the drivers of energy use were discussed, and discussions were analysed using a framework of a successful existing behavioural model - the Comprehensive Action Determination Model - that includes both conscious and unconscious drivers of energy consumption. The findings show (1) participants did not tend to believe they saved energy to conserve the environment, (2) adherence to egoistic values, apparent in the lack of motivation to save energy in the absence of financial incentives, and (3) strong awareness of energy habits. Policy makers targeting young adults' energy use are advised how to align energy policy with these perceptions.